Warrior mindset mental toughness skills for a nation's defenders : performance psychology applied to combat - Asken, Michael J.; Christensen, Loren W.; Grossman, Dave (Human Factor Research Group, 2010)
Mental toughness is esssential for elite human performance and especially in high stress situations. While mental toughness is a singular value in both military and law enforcement training and missions, too often, there is a disconnect between tallking about and actually training it. Warrior MindSet defines mental toughness and describes its critical need and function in the face of the performance degrading effects of combat, mission or response stress. Warrior MindSet provides the psychological skills that comprise mental toughness to optimze performance, success, safety and survival in the field.